BDNF/trkB Induction of Calcium Transients through Cav2.2 Calcium Channels in Motoneurons Corresponds to F-actin Assembly and Growth Cone Formation on β2-Chain Laminin (221) - Dombert, Benjamin; Balk, Stefanie; Lüningschrör, Patrick; Moradi, Mehri; Sivadasan, Rajeeve; Saal-Bauernschubert, Lena; Jablonka, Sibylle (Frontiers in Molecular Neuroscience, 2017)
Spontaneous Ca2+ transients and actin dynamics in primary motoneurons correspond to cellular differentiation such as axon elongation and growth cone formation. Brain-derived neurotrophic factor (BDNF) and its receptor trkB support both motoneuron survival and synaptic differentiation. However, in motoneurons effects of BDNF/trkB signaling on spontaneous Ca2+ influx and actin dynamics at axonal growth cones are not fully unraveled. In our study we addressed the question how neurotrophic factor signaling corresponds to cell autonomous excitability and growth cone formation. Primary motoneurons from mouse embryos were cultured on the synapse specific, β2-chain containing laminin isoform 221 regulating axon elongation through spontaneous Ca2+ transients that are in turn induced by enhanced clustering of N-type specific voltage-gated Ca2+ channels (Cav2.2) in axonal growth cones. TrkB deficient (trkBTK-/-) mouse motoneurons which express no full-length trkB receptor and wildtype motoneurons cultured without BDNF exhibited reduced spontaneous Ca2+ transients that corresponded to altered axon elongation and defects in growth cone morphology which was accompanied by changes in the local actin cytoskeleton. Vice versa, the acute application of BDNF resulted in the induction of spontaneous Ca2+ transients and Cav2.2 clustering in motor growth cones, as well as the activation of trkB downstream signaling cascades which promoted the stabilization of β-actin via the LIM kinase pathway and phosphorylation of profilin at Tyr129. Finally, we identified a mutual regulation of neuronal excitability and actin dynamics in axonal growth cones of embryonic motoneurons cultured on laminin-221/211. Impaired excitability resulted in dysregulated axon extension and local actin cytoskeleton, whereas upon β-actin knockdown Cav2.2 clustering was affected. We conclude from our data that in embryonic motoneurons BDNF/trkB signaling contributes to axon elongation and growth cone formation through changes in the local actin cytoskeleton accompanied by increased Cav2.2 clustering and local calcium transients. These findings may help to explore cellular mechanisms which might be dysregulated during maturation of embryonic motoneurons leading to motoneuron disease.